Bulb Canker of Garlic Caused by Embellisia allii, Newly Found in Nepal - Timila, Ramesh D.; Manandhar, Gyanu; Joshi, Sharada (Nepal Agriculture Research Journal, 2014)
N/A Nepal Agric. Res. J. Vol. 8, 2007, pp. 127-129 DOI: http://dx.doi.org/10.3126/narj.v8i0.11606